Pulmonary artery imaging with 68 Ga-FAPI-04 in patients with chronic thromboembolic pulmonary hypertension - Gong, Juan-Ni; Chen, Bi-Xi; Xing, Hai-Qun; Huo, Li; Yang, Yuan-Hua; Yang, Min-Fu (Journal of nuclear cardiology, 2023)
The feasibility and significance of imaging pulmonary artery (PA) remodeling with 68 Ga-fibroblast activating protein inhibitor (FAPI) in patients with chronic thromboembolic pulmonary hypertension (CTEPH) have not yet been addressed. 68 Ga-FAPI-04 uptake in the PA and ascending artery was evaluated in 13 patients with CTEPH and 13 matched non-CTEPH controls. The correlations of PA 68 Ga-FAPI-04 uptake and remodeling parameters derived from right heart catheterization (RHC) were analyzed. Of the 13 patients with CTEPH, nine (69%) showed visually enhanced 68 Ga-FAPI-04 uptake, whereas none of the control subjects had increased 68 Ga-FAPI-04 uptake in the PA. The prevalence of enhanced uptake in the main, lobar, and segmental PAs was 45% (17/38), 33% (16/48), and 28% (44/159), respectively. 68 Ga-FAPI-04 activity in the PA was positively correlated with pulmonary arterial diastolic pressure (r = 0.571, P = 0.041). 68 Ga-FAPI-04 has the potential for imaging fibroblast activation in the PA wall, and 68 Ga-FAPI-04 activity in PA is positively correlated with pulmonary arterial diastolic pressure. ▪